(untitled) (Economics and region, 2022)
External and internal financial relations of insurance companies determine the need for effective financial management. Using world experience and taking into account domestic features will allow responding to changes in the external environment and the internal state of the insurer. The purpose of the article is to deepen the theoretical foundations and substantiation of organizational aspects of financial management of a domestic insurance company. The article states that insurance companies create costs and receive income in their activities. The article emphasizes that a feature of the insurance process is that the insured’s funds are paid in advance during the formation of insurance reserves and are temporarily held by the insurer, who places and uses them for the purpose of ensuring insurance payments and obtaining a certain income. It is noted that a certain guarantee is necessary regarding the ability of the insurer to fulfill its obligations within the limits of the risks accepted for insurance and the scope of responsibility for them. In the article, the financial stability of the insurance company is considered from the following main points: the probability of a lack of funds in any period; financial strength of the insurance fund; profitability of the entire activity of the insurance company.